SOCIO PRAGMATICS ANALYSIS ON WARNING UTTERANCES IN HUMOROUS ACTION MOVIE MANUSCRIPTS AND ITS SUBTITLINGS - SETIOWATI , RENI DIAH (2011)
This research aims at describing the variations of language form, the equivalence implicature, and the politeness strategies of warning utterances used in humorous action movie manuscripts and its subtitling. The type of this research is descriptive qualitative. The technique of collecting data is documentation method, and the steps are watching the original movies, noting, retyping, coding, and analyzing the data of warning utterances and its subtitling. To achieve the objectives the writer refers to linguistics form theory to identify the variation of language form in warning utterances and its subtitling, Grice's theory of implicature to clarify the equivalence and non equivalence implicature, and to describe the equivalence and non equivalence Politeness strategies, the writer applies Brown and Levinson theory of politeness. The result of the study shows that the language form of warning utterances in humorous action movie manuscripts and its subtitling are 3,7% word is subtitled into word, 1,85% word is subtitled into phrase, 3,7% phrase is subtitled into phrase, 1,85% phrase is subtitled into word, 11,1% positive declarative sentence is subtitled into positive declarative sentence, 7,41% negative declarative sentence is subtitled into negative declarative sentence, 3,7% negative imperative sentence is subtitled into negative imperative sentence, 11,1% positive imperative sentence is subtitled into positive imperative sentence, 3,7% positive interrogative sentence is subtitled into positive interrogative sentence, 22,22% positive exclamatory sentence is subtitled into positive exclamatory sentence, 18,52% negative exclamatory sentence is subtitled into negative exclamatory sentence, 5,56% positive conditional sentence is subtitled into positive conditional sentence, 1,85% positive declarative sentence is subtitled into negative imperative sentence, and 3,7% positive exclamatory sentence is subtitled into positive declarative sentence. The implicature use on warning utterances and its subtitling is 100% conversational implicature in the form of equivalence implicature. The politeness strategies are 33,33% bald on record, 27,78% positive politeness, 16,67% negative politeness, and 20,37% off record strategy in the form of equivalent and 1, 85% non equivalent of bald on record.